ANALISIS PENATAAN DAERAH DI PROVINSI JAWA BARAT - Sulthon Rohmadin; Dedi Kusmana; Yusi Eva Batubara (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2017)
The research undertaken has the objective to analyze the wide area, demography and area coverage in order to provide policy recommendations related to the regulation of regency in West Java Province as mandated by UU 23 Tahun 2014 tentang Pemerintahan Daerah. This study used tailor made method which directs a comprehensive study results become a major consideration for policy makers in the formulation of policy. The results of the analysis show that only Bogor Regency has the most complete feasibility to be expanded into district and city compared to other districts in West Java. While Cianjur, Bekasi and Garut have the feasibility to form City. Keywords: regional arrangement, DOB formation